CAD-Integrated Parametric Lightweight Design With Isogeometric B-Rep Analysis - Goldbach, Ann-Kathrin; Bauer, Anna M.; Wüchner, Roland; Bletzinger, Kai-Uwe (Frontiers in Built Environment, 2020)
The complex geometries of lightweight structures can easily be modeled with modern CAD systems that use NURBS. Isogeometric B-Rep Analysis (IBRA) adopts the NURBS geometries along with their topology for the analysis model, which can thus fulfill both design purposes and solve structural problems in one software environment. Especially in lightweight design, which is characterized by a strong interaction between shape and structural behavior, this presents a major advantage. Results can be used as a new input to consecutive analyses within this novel approach. This is especially useful for the simulation of construction stages or in the design cycle of membrane structures, where mechanically driven optimizations such as formfinding and cutting pattern generation, as well as structural analysis, are dependent on each other. This paper focusses on parametric design with IBRA and the advantages of the uniform model description and workflow. Not only geometrical but also mechanical properties can be parameterized and thus offer a large variety of options to explore for designers as well as engineers. In addition to the possibility of optimization through formfinding methods, the provided framework can conveniently be combined with other tools and thus be extended by external optimization loops where geometry and structural parameters are modified simultaneously. The successful integration of parametric IBRA in a CAD environment such as Rhino and Grasshopper is presented. Selected examples demonstrate the significance of the CAD-integrated unified workflow for the interactive analysis loops of lightweight structures.